FISHERY AND BIOLOGY OF WHITE SARDINE, ESCUALOSA THORACATA (VALENCIENNES) AT VERSOVA, BOMBAY - RAJE, S. G.; DESHMUKH, V. D.; THAKURDAS, THAKURDAS (Journal of Indian Fisheries Association, 2015)
Gill net fishery exclusively for the white sardine, Escualosathoracata, which started in mid eighties at Versova, is described.During 1987-88 to 1991-92 period the annual average landing of thespecies was 202.2 tons with year to year fluctuations. The peak fishingseason was during April-May. The size range of the species in the gillnet was 41-105 mm and the von Bertalanffy growth parameters, Looand K, estimated by the ELEFAN programme were 110 mm and 1.8 peryear. The length-weight relationship was W = 0.000001508 L 3.3946 forthe males and W = 0.000002561 L 3.2706 for the females. The foodconsisted of copepods, cladocerans and crustacean larvae. The size atmaturity for the females was 82 mm and spawning took place duringOctober Â· February period. The sex-ratio showed equal proportionexcept during January, July and October when females dominated inthe catch.